ANALISIS PENERAPAN ASEAN-INDIA FREE TRADE AREA (AIFTA) TERHADAP PERDAGANGAN DUA NEGARA INDONESIA DENGAN INDIA MENGGUNAKAN GRAVITY MODEL - Janes Guratan Djermor; Ivan Yulianto (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2018)
The ASEAN-India Free Trade Area (AIFTA) policy has been effectively run since January 1, 2010. It is time to evaluate its benefits for trade relations between its members, especially between Indonesia and India. Analysis of the effectiveness and benefits of AIFTA policy in this study uses the Gravity Model by calculating the variables of Indonesia's GDP, India's GDP, transportation costs, and AIFTA's policies enggaged in trade relations between Indonesia and India using data from first quarter of 2004 until first quarter of 2018. This research shows that implementation of AIFTA does not have any effect on trade between two countries since trade between them had already reaching normal level. This research wishes to give a better insight on policy taking, especially for ongoing and forthcoming trade agreement.